IMPROVEMENT OF LABORATORY SERVICE QUALITY OF OUTPATIENT INSTALLATION AT SEMEN GRESIK HOSPITAL BY QUALITY FUNCTION DEPLOYMENT (QFD) METHOD (Proceedings of the International Conference on Public Health, 2017)
A Quality Assessment in a hospital is very important to be done. In 2014, the level of patients’ satisfaction in the Outpatient Installation of Semen Gresik Hospital was low with an average reaching 73.75% compared with Hospital Minimum Service Standard i.e. by ≥ 90%. This research aimed to arrange a recommendation of the quality improvement of laboratory services in the Outpatient Installation of Semen Gresik Hospital with Quality Function Deployment (QFD) method. This research was an analytic observational research using Cross Sectional method in data collection. The research was conducted from April to September 2015.  Respondents of this research were patients who received more than twice services at the Outpatient Installation of Semen Gresik Hospital. The final result of this research of Quality Function Deployment (QFD) method is House of Quality (HoQ) of Laboratory service in Outpatient Installation of Semen Gresik Hospital. The conclusion of the research was that the first priority of Customers’ Needs of Laboratory service was that the result waiting time in laboratory became faster. The recommendation given was to increase supervision role, to evaluate the SOP of the result waiting time, to increase the staff competency, to optimize the existing facilities and to make laboratory direction of outpatient installation.
Keywords: Quality Function Deployment, Laboratory, Outpatient Installation, Customer Service